Genotoxic and Anti-Genotoxic Potential of Hydrosols from Water-Steam Distillation of Oil-Bearing Roses Rosa centifolia L. and Rosa gallica L. from Bulgaria - Svetla Gateva; Gabriele Jovtchev; Tsveta Angelova; Tsvetelina Gerasimova; Ana Dobreva; Milka Mileva (MDPI AG, 2024)
Rosa centifolia L. and Rosa gallica L. (Rosaceae) are grown as raw materials for valuable essential oils and hydrosols. There are scarce data about the biological activities and the genoprotective potential of the hydrosols of these roses. The aim of the study was to provide information on their cytotoxic/genotoxic activity and anti-cytotoxic/anti-genotoxic capacity against mutagenic N-methyl-N'-nitro-N-nitrosoguanidine (MNNG). The evaluation was performed using classical tests for chromosomal aberrations and micronuclei in the higher plant Hordeum vulgare and human lymphocyte test systems. The experimental schemes included combined hydrosol and mutagen treatment. Both hydrosols (6, 14, 20%) had no cytotoxic effect on barley and showed low genotoxicity in both test systems as the injuries were enhanced to a lesser extent compared to the controls. Lymphocytes were more susceptible than H. vulgare. Under the conditions of combined treatment, it was found that the two hydrosols possessed good anti-cytotoxic and anti-genotoxic potential against MNNG. Both rose products exerted genoprotective potential to a similar extent, decreasing the frequencies of aberrations in chromosomes and micronuclei to a significant degree in both types of cells when non-toxic concentrations of hydrosols were applied before MNNG. This was performed both with and without any inter-treatment time. The observed cytoprotective/genoprotective potential suggests that these hydrosols are promising for further application in phytotherapy and medicine.